Therapeutic Approach against 2019-nCoV by Inhibition of ACE-2 Receptor - Kumar, Gajendra; Kumar, Dharmendra; Singh, Netra Pal (Drug Research, 2020)
The continued spread of 2019-nCoV has prompted widespread concern around the world. WHO formally named COVID-19 and International Committee on Taxonomy called it Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Due to this viral attack, the whole world is in lockdown. Presently, there is no effective way to control it, except social distancing and hygienic activity. World class scientists and researchers are trying to make vaccine and discover the medicine against the control and cure to this deadly viral disease. Our aim to presenting this article is kick-off deadly viral disease i.e COVID-19 by an easy way with minimum intervention and effort. Different ayurvedic therapeutic agents (Curcuma Longa L, Green tea and Piper nigrum) inhabit entry of virus in host cell, transmission of pathogen and improve the immunity. Curcumin and piperine (1-piperoylpiperidine) interact to each other and form a π—π intermolecular complex which enhance the bioavailability of curcumin by inhibition of glucuronidation of curcumin in liver. Both the molecules curcumin and catechin get bound directly to receptors binding domain of S-protein and ACE-2 receptors of host cell, due to which these molecules inhibit the entry of virus in host cell i. e. animal survives from being infected.
Keywords: antiviral drug; 2019 nCoV; curcumin; catechin; 1-piperoylpiperidine; ACE-2 inhibitor